2006
DOI: 10.1128/jvi.00361-06
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Polypurine Tracts Affect Rous Sarcoma Virus Integration In Vivo

Abstract: When the endogenous polypurine tract (PPT) of the Rous sarcoma virus (RSV)-derived vector RSVP(A)Z was replaced with alternate retroviral PPTs, the fraction of unintegrated viral DNA with the normal consensus ends significantly decreased and the retention of part of the PPT significantly increased. If the terminus of the U3 long terminal repeat (LTR) is aberrant, RSV integrase can correctly process and integrate the normal U5 LTR into the host genome. However, the canonical CA is not involved in joining the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Genomic DNA was isolated from infected DF-1 (24,25) cells that survived zeocin selection using a QIAamp DNA blood maxikit (Qiagen). To recover full-length proviruses, 100 to 200 g of genomic DNA was digested with DraI overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was isolated from infected DF-1 (24,25) cells that survived zeocin selection using a QIAamp DNA blood maxikit (Qiagen). To recover full-length proviruses, 100 to 200 g of genomic DNA was digested with DraI overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…DNA end processing prior to SSC formation could account for the different apparent rates of U5 versus U3 cleavage during HIV-1 infection (31) and is consistent with integrase-mediated integration of the sole wild type ends of single LTR end mutant viruses (128,129). However, 3′ processing and strand transfer of single viral DNA ends can occur in the context of the SSC in vitro (120).…”
Section: Integrase Functions As a Multimermentioning
confidence: 99%
“…Titers of viruses that contained one mutated LTR end were modestly reduced, whereas double end-mutant viruses were essentially dead (11,12,127). Sequence analysis revealed large insertions or deletions of cellular DNA associated with the integration of mutant LTR ends (128,129). Though virus replication normally proceeds through the pairwise insertion of both LTRs (Fig.…”
Section: Integrase Functions As a Multimermentioning
confidence: 99%
“…Consistent with the observation that the NTD works in trans with the CCD to catalyze 3Ј-processing activity (27,28), Li et al (24) demonstrated that a single HIV-1 DNA end can moreover be processed and integrated in the context of the intasomal tetramer in vitro. Such asymmetry may very well account for the different rates at which the U3 versus U5 ends of the HIV-1 LTR are processed during acute infection (3), as well as for the reasonable titers of single LTR end mutant viruses (53,54), where IN-mediated integration of the wild-type end presumably templates subsequent host-mediated integration of the mutant viral DNA end (55,56). Skalka and co-workers (57) have interestingly reported a novel "reaching dimer" structure for avian sarcoma virus IN protein based on small-angle x-ray scattering and chemical cross-linking that mimics the extended inner monomers of the PFV intasome.…”
Section: Retroviral In-dna Nucleoprotein Complexesmentioning
confidence: 99%